Social capital in Islamic community-based pesantren - Nabila Tahira; Kurnia Asni Sari; Ainul Zulqoifah Asmawati; Suci Wahyu Fajriani (Priviet Social Sciences Journal, 2025)
Pesantren is one of the oldest educational institutions in Indonesia. This study aims to analyze how social capital contributes to economic independence at Pesantren Aulia Cendekia in Palembang, Indonesia. This is due to limited funding sources and competition among educational institutions. Pesantren, as an institution with a unique educational program centered on religious teaching, uses social capital to maintain financial sustainability by utilizing business units within the institution. This study examines the assets of pesantren business units using Robert D. Putnam's social capital theory, which links social capital with economic independence. With a comprehensive and contextual approach, this study uses qualitative methodology and collects data through observation, interviews, and documentation. The results show that the economic success of pesantren depends not only on their tangible assets but also on the quality of connections, teamwork, and important figures such as ustadz. Using sustainable business units, such as managing productive waqf (Islamic endowment funds), establishing business incubators, and forming Micro Waqf Banks in collaboration with the government, Islamic boarding schools utilize their social capital, which includes alumni networks and trust. In addition to business units, the ustad also plays an important role in the sustainability of Islamic boarding schools in terms of their economic independence.